A Monoclonal Antibody to Platelet Type III Collagen-binding Protein (TIIICBP) Binds to Blood and Vascular Cells, and Inhibits Platelet Vessel-wall Interactions - Monnet, Emmanuel; Depraetere, Hilde; Legrand, Chantal; Deckmyn, Hans; Fauvel-Lafève, Françoise (Thrombosis and Haemostasis, 2001)
TIIICBP is a new platelet receptor involved in platelet-type III collagen and platelet-subendothelium interactions. This receptor is composed of a doublet of 72-68 kDa proteins. In this study, the major protein (68 kDa) was purified and used to produce monoclonal antibodies. One of these antibodies, 7F4, binds to platelets as confirmed by flow cytometry. 7F4 inhibited platelet contact, spreading and aggregation induced by type III collagen. Under flow conditions, 7F4 prevented platelet interactions with type III collagen, endothelial cell matrix and the KOGEOGPK type III collagen octapeptide: the specific sequence recognized by TIIICBP. On the other hand, 7F4 had no effect on platelet-type I collagen interactions. TIIICBP was also detected on lymphocytes, granulocytes and monocytes. TIIICBP was expressed on endothelial cells and fibroblasts but not on smooth-muscle cells. These results show that TIIICBP is expressed on several cell types and participates in cell adhesion to the subendothelium.
Keywords: Collagen receptor; platelet adhesion; subendothelium; type III collagen; leukocytes